The effect of economic growth level, trade openness, FDI on tax revenues in four low-income countries in Southeast Asia - Le, Thi Mai Huong; Tran, Van Hung (Edelweiss Applied Science and Technology, 2024)
The study aims to analyze the impact of economic growth level, trade openness, and FDI capital on tax revenue in four low-income Southeast Asian countries including Vietnam, Laos, Cambodia, and Myanmar. Secondary data was collected from the World Bank between 2000 and 2022. The data panel was analyzed using the Pooled OLS retrieval model. The research results indicate a significant impact of GDP per capita, trade openness, and FDI on tax revenue in these four nations. Consequently, this result aligns with previous studies. The article suggests recommendations to increase tax revenue for these countries.